2020
DOI: 10.3390/ani10030372
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification Impacts of Ascorbic Acid and Clay on Laying Japanese Quail Fed Diets Polluted by Various Levels of Cadmium

Abstract: A total number of 360 laying Japanese quail (8 weeks of age) were randomly divided into 12 groups. Birds in all groups had nearly the same average initial body weight. A factorial arrangement (4 × 3) was performed including four levels of dietary cadmium (Cd) as cadmium chloride (0, 50, 100, and 150 mg/kg diet) and three levels of feed additives (without, 300 mg/kg ascorbic acid and 1.50% natural clay). Results revealed that Cd contaminated feed caused significant (p < 0.01) retardation in body weight, lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
2
12
0
Order By: Relevance
“…In a lifelong experiment [9] evaluating the survival of animals exposed to cadmium, more individuals survived (one-year survival was also 100% as confirmed by the experiments) compared to other heavy metals. This may be because cadmium in low doses may function as an essential element [10][11][12]. Hijová et al [13] also did not report any death of exposed animals during a chronic experiment in rats lasting 90 days, administering CdCl 2 in drinking water per os with a predicted daily dose of cadmium of 2.5 mg•kg −1 , similar to this study.…”
Section: Toxicological Parameterssupporting
confidence: 83%
“…In a lifelong experiment [9] evaluating the survival of animals exposed to cadmium, more individuals survived (one-year survival was also 100% as confirmed by the experiments) compared to other heavy metals. This may be because cadmium in low doses may function as an essential element [10][11][12]. Hijová et al [13] also did not report any death of exposed animals during a chronic experiment in rats lasting 90 days, administering CdCl 2 in drinking water per os with a predicted daily dose of cadmium of 2.5 mg•kg −1 , similar to this study.…”
Section: Toxicological Parameterssupporting
confidence: 83%
“…Furthermore, feedstuffs, drinking water, inspired cigarette smoke or polluted air, and absorption of polluted soil and dust created by people and animals that have earlier collected Cd in their biological cells are also causes of Cd exposure [ 7 ]. Indeed, Cd is a non-biodegradable, poisonous element with a prolonged biological half-life and is harmful to plants, humans, and animals [ 8 ]. Several attempts by national organizations and government agencies to limit Cd usage have been applied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite low concentrations of Cd subjection in the renal tissue, it accumulates in the tubular epithelium in the form of a Cd-metallothionein complex, leading to proximal tubular dysfunction [ 8 ]. Several experiments have shown that Cd-stimulated renal toxicity is mediated by the liberation of Cd-metallothionein compounds from impaired Kupffer cells, which are refined by the glomerulus, endocytosed through the proximal tubular cells, and destroyed by lysosomes after Cd accumulation [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are only a few studies on egg quality parameters of cadmium. Abou-Kassem et al [4] reported that ascorbic acid or natural clay decreases the negative effects of Cd and improves some egg quality traits of laying Japanese quails. Korénekova et al [23] found that Cd (0.12 mg/day per quail) had adverse effects on the quality parameters of eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Cadmium toxicity causes oxidative stress, an increase in metallothionein synthesis, as well as impairment in Zn, Ca, and Fe metabolism, enzyme functions, and plasma membrane integrity. Vitamins, minerals, and herbs have been studied to reduce the negative effects of cadmium, but few studies have been conducted on poultry [1,3,4,5]. Based on these studies, it has been reported that some dietary supplements may be effective against cadmium toxicity.…”
Section: Introductionmentioning
confidence: 99%